Pengabdian kepada Masyarakat melalui Kuliah Kerja Nyata (KKN) di Dusun IV, Desa Tuntungan II, Kabupaten Deli Serdang - Yusnidar Sari Mutiara; Reni Agustina Harahap; Nayla Indah Syaputri; Nanda Fadillah Darus; Mufidah Harahap; Linda Liswana; Yeni Sabariah; Supangge Tiara (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2025)
Community Service Program (Kuliah Kerja Nyata/KKN) is a community service program integrated into the higher education curriculum, aiming for students to apply theoretical knowledge into real-world practice and contribute to community development and empowerment. This KKN activity was carried out in Dusun IV, Tuntungan II Village, Deli Serdang Regency, from July 1 to August 1, 2025. The main objective of this program was to address various local issues such as limited use of appropriate technology, low environmental awareness, and a lack of human resource development. The method used was field observation to ensure that the programs implemented were in line with the community's needs and potential. Various activities were carried out, including community clean-up (gotong royong), teaching at elementary schools, health counseling for mothers and the elderly, Qur'an recitation lessons for children, compost making, planting a "living pharmacy" (apotek hidup), and assisting with UMKM product marketing. The results of this program showed a positive impact, such as increased community knowledge of health, environmental cleanliness, and the use of organic fertilizer. Furthermore, UMKM assistance successfully improved business owners' understanding of digital marketing. Overall, this KKN activity successfully created synergy between the university, the village government, and the community, while also providing valuable experience for students in leadership and teamwork.